Автоматизоване проектування та розпаралелювання програм для гетерогенних платформ із використанням алгебро-алгоритмічного інструментарію - Дорошенко, А.Ю.; Бекетов, О.Г.; Бондаренко, М.Н.; Яценко, О.Я. (Проблеми програмування, 2020)
Запропоновані методи та інструментальні засоби автоматизованого проектування та генерації OpenCL програм на основі алгебри алгоритмів. Розроблено метод напівавтоматичного розпаралелювання циклічних операторів на основі серіалізації даних. Розглянутий підхід полягає у використанні високорівневих алгебро-алгоритмічних специфікацій програм, що подаються у природно-лінгвістичній формі. Розроблені інструментальні засоби забезпечують автоматизоване проектування схем алгоритмів шляхом суперпозиції конструкцій алгебри Глушкова. Інструментарій автоматично виконує генерацію програм цільовою мовою програмування на снові специфікацій. Розроблений програмний засіб паралелізації циклів для оптимізації обчислень за допомогою графічних прискорювачів дозволяє в напівавтоматичному режимі здійснювати перехід від послідовних до паралельних програм і використовує систему переписувальних правил для трансформації програм. Застосування підходу проілюстроване на розробці паралельної OpenCL програми згортки зображень. Предложены методы и инструментальные средства автоматизированного проектирования и генерации OpenCL программ на основе алгебры алгоритмов. Разработан метод полуавтоматического распараллеливания циклических операторов с использованием сериализации данных. Рассмотренный подход заключается в использовании высокоуровневых алгебро-алгоритмических спецификаций программ, которые представляются в естественно-лингвистической форме. Разработанные инструментальные средства обеспечивают автоматизированное проектирование схем алгоритмов путем суперпозиции конструкций алгебры Глушкова. Инструментарий автоматически выполняет генерацию программ на целевом языке программирования на основе спецификаций. Разработанное программное средство параллелизации циклов для оптимизации вычислений с использованием графических ускорителей позволяет в полуавтоматическом режиме осуществлять переход от последовательных к параллельным программам и использует систему переписывающих правил для трансформации программ. Применение подхода проиллюстрировано на разработке параллельной OpenCL программы свертки изображений. Methods and software tools for automated design and generation of OpenCL programs based on the algebra of algorithms are proposed. OpenCL is a framework for developing parallel software that executes across heterogeneous platforms consisting of general-purpose processors and/or hardware accelerators. The proposed approach consists in using high-level algebra-algorithmic specifications of programs represented in natural linguistic form and rewriting rules. The developed software tools provide the automated design of algorithm schemes based on a superposition of Glushkov algebra constructs that are considered as reusable components. The tools automatically generate code in a target programming language on the basis of the specifications. In most computing problems, a large part of hardware resources is utilized by computations inside loops, therefore the use of automatic parallelization of cyclic operators is most efficient for them. However, the existing automatic code parallelizing tools, such as Par4All, don’t account the limited amount of accelerator’s onboard memory space while real-life problems demand huge amounts of data to be processed. Thus, there is a need for the development of a parallelization technique embracing the cases of massive computational tasks involving big data. In the paper, a method and a software tool for semi-automatic parallelization of cyclic operators based on loop tiling and data serialization are developed. The parallelization technique uses rewriting rules system to transform programs. The framework for parallelization of loops for optimization of computations using graphics processing units allows semi-automatic parallelization of sequential programs. The approach is illustrated on an example of developing a parallel OpenCL image convolution program.